Intensive Lactation Counseling for The Success of Giving Exclusive Breastfeeding until 2 Months Old - Nurdiana Nurdiana; Kamilah Budhi; Mateus Sakundarno; Maria Mexitalia; Bagoes Widjanarko (Humanistic Network for Science and Technology (HNST), 2018)
Background: In Semarang in 2016, giving exclusive breastfeeding by mother to her baby was 67.16% and in work area of Candi Lama Public Health Center only reached 43.52%. So far, it had not been known the influence of intensive lactation counseling against the success of giving exclusive breastfeeding. Purpose: to know the influence of intensive lactation counseling against the success of giving exclusive breastfeeding until 2 months old. Methods: This research utilized quasi experimental design. Population in this research was mothers who had gestational age in 37-42 weeks. Total of the subjects was 32 mothers who were divided by 2 groups, experiment group (n = 16) and control group (n = 16). Experiment group was given intensive lactation counseling in 6 times for 3 months. Meanwhile, control group was not given any lactation counseling, but was given leaflet of exclusive breastfeeding. Results: Proportion of mothers who were successful in giving exclusive breastfeeding until 2 months old in experiment group was higher (93.75%) rather than in control group (31.25%). The difference in this proportion was quite significant (p= 0.001). The comparison result of proportion for mothers who were successful in giving exclusive breastfeeding until 2 months old between the group that was given intensive lactation counseling (experiment group) and control group showed RR = 3.0 (95% CI: 1.435-6.273). Conclusion: Giving intensive lactation counseling increased the proportion for the mothers who were successful in giving exclusive breastfeeding until 2 months old. Keywords: Intensive lactation counseling, Exclusive breastfeeding